Reduced cleavage of von willebrand factor by ADAMTS13 is associated with microangiopathic acute kidney injury following trauma. Issue 1 (January 2022) - Plautz, William E.; Haldeman, Shannon H.; Dyer, Mitchell R.; Sperry, Jason L.; Guyette, Francis X.; Loughran, Patricia A.; Alvikas, Jurgis; Hassoune, Adnan; Hoteit, Lara; Alsaadi, Nijmeh; Zuckerbraun, Brian S.; Rollins-Raval, Marian A.; et al.
Abstract : N/A: Acute kidney injury (AKI) is common after trauma, but contributory factors are incompletely understood. Increases in plasma von Willebrand Factor (vWF) with concurrent decreases in ADAMTS13 are associated with renal microvascular thrombosis in other disease states, but similar findings have not been shown in trauma. We hypothesized that molecular changes in circulating vWF and ADAMTS13 promote AKI following traumatic injury. VWF antigen, vWF multimer composition and ADAMTS13 levels were compared in plasma samples from 16 trauma patients with and without trauma-induced AKI, obtained from the Prehospital Air Medical Plasma (PAMPer) biorepository. Renal histopathology and function, vWF and ADAMTS13 levels were assessed in parallel in a murine model of polytrauma and haemorrhage. VWF antigen was higher in trauma patients when compared with healthy controls [314% (253–349) vs. 100% (87–117)] [median (IQR)], while ADAMTS13 activity was lower [36.0% (30.1–44.7) vs. 100.0% (83.1–121.0)]. Patients who developed AKI showed significantly higher levels of high molecular weight multimeric vWF at 72-h when compared with non-AKI counterparts [32.9% (30.4–35.3) vs. 27.8% (24.6–30.8)]. Murine plasma cystatin C and vWF were elevated postpolytrauma model in mice, with associated decreases in ADAMTS13, and immunohistologic analysis demonstrated renal injury with small vessel plugs positive for fibrinogen and vWF. Following traumatic injury, the vWF-ADAMTS13 axis shifted towards a prothrombotic state in both trauma patients and a murine model. We further demonstrated that vWF-containing, microangiopathic deposits were concurrently produced as the prothrombotic changes were sustained during the days following trauma, potentially contributing to AKI development. Abstract : Supplemental Digital Content is available in the text